The culture of education - Bruner, Jerome Seymour, 1915- (Harvard University Press, 1996)
What we don't know about learning could fill a book - and it might be a schoolbook. In a masterful commentary on the possibilities of education, the eminent psychologist Jerome Bruner reveals how education can usher children into their culture, though it often fails to do so. Applying the newly emerging "cultural psychology" to education, Bruner proposes that the mind reaches its full potential only through participation in the culture - not just its more formal arts and sciences, but its ways of perceiving, thinking, feeling, and carrying out discourse. By examining both educational practice and educational theory, Bruner explores new and rich ways of approaching many of the classical problems that perplex educators.<U+000d><U+000a><U+000d><U+000a>Going well beyond his earlier acclaimed books on education, Bruner looks past the issue of achieving individual competence to the question of how education equips individuals to participate in the culture on which life and livelihood depend. Educators, psychologists, and students of mind and culture will find in this volume an unsettling criticism that challenges our current conventional practices - as well as a wise vision that charts a direction for the future.